Peran Tawakkal dalam Meningkatkan Kesejahteraan Psikologis Mahasiswi Ibu Rumah Tangga yang Mengalami Kecemasan: Perspektif Psikologi Islam - Rina Melati; Ummu Khuzaimah (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the relationship between tawakkal (trustful reliance upon Allah) and psychological well-being among married female students who also perform the role of housewives while pursuing online learning. The transition to online education has intensified multiple role demands, which may contribute to anxiety, fatigue, and diminished well-being. Within Islamic psychology, tawakkal is viewed as a religious coping orientation that may support emotional regulation, meaning-making, and resilience in stressful circumstances. Therefore, this research aimed (1) to describe levels of tawakkal and psychological well-being and (2) to test whether tawakkal is significantly associated with psychological well-being in this population. A quantitative correlational, cross-sectional design was employed. A total of 102 respondents were recruited using purposive sampling. Data were collected online between 25 November and 2 December 2025 using Likert-type questionnaires measuring tawakkal (14 items; Cronbach’s α = .646) and psychological well-being (12 items; α = .459). Descriptive results indicated moderate-to-high mean scores for tawakkal (M = 3.511, SD = 0.456) and psychological well-being (M = 3.587, SD = 0.378). Shapiro–Wilk testing showed that tawakkal scores were not normally distributed (p = .003); therefore, Spearman’s rank correlation was applied. The findings revealed a positive, statistically significant association between tawakkal and psychological well-being (ρ = .350, p < .001). These results suggest that higher tawakkal is related to higher psychological well-being among married female online learners. Practical implications include integrating tawakkal-based strengthening strategies into counseling and psycho-spiritual support services, while further research is recommended to employ instruments with stronger reliability and to include anxiety-related measures for deeper explanation.